Biphenotypic lung carcinoma with coexpression of TTF-1 and ΔNP63/P40 within most of the same individual cells: a further case confirming poor prognosis and a review of literature - Marando, Alessandro; Zagni, Moreno; Negrelli, Mariachiara; Valtorta, Emanuele; Lauricella, Calogero; Motta, Valentina; Veronese, Silvio; Cerea, Giulio; Giannetta, Laura Giuseppina; Ciarlo, Gabriele; Signorelli, Diego; Pizzutilo, Elio Gregory; et al. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2024)
The WHO Classification of Tumors, Thoracic Tumors, 5th edition, has outlined the use of TTF-1 and ∆NP63/P40 to discriminate between adenocarcinoma and squamous cell carcinoma. In 2015, the first description of a rare non-small cell lung carcinoma featuring co-expression of glandular and squamous differentiation within most of the same individual tumor cells was reported on, with ultrastructural and molecular demonstration of such a biphenotypic differentiation. We herein describe an additional case of this rare tumor entity, which is confirmed to be an aggressive neoplasm despite potential targets of therapy.